Diversity of Chemical Structures and Biosynthesis of Polyphenols in Nut-Bearing Species - Aneklaphakij, Chaiwat; Saigo, Tomoki; Watanabe, Mutsumi; Naake, Thomas; Fernie, Alisdair R.; Bunsupa, Somnuk; Satitpatipan, Veena; Tohge, Takayuki (Frontiers in Plant Science, 2021)
Nuts, such as peanut, almond, and chestnut, are valuable food crops for humans being important sources of fatty acids, vitamins, minerals, and polyphenols. Polyphenols, such as flavonoids, stilbenoids, and hydroxycinnamates, represent a group of plant-specialized (secondary) metabolites which are characterized as health-beneficial antioxidants within the human diet as well as physiological stress protectants within the plant. In food chemistry research, a multitude of polyphenols contained in culinary nuts have been studied leading to the identification of their chemical properties and bioactivities. Although functional elucidation of the biosynthetic genes of polyphenols in nut species is crucially important for crop improvement in the creation of higher-quality nuts and stress-tolerant cultivars, the chemical diversity of nut polyphenols and the key biosynthetic genes responsible for their production are still largely uncharacterized. However, current technical advances in whole-genome sequencing have facilitated that nut plant species became model plants for omics-based approaches. Here, we review the chemical diversity of seed polyphenols in majorly consumed nut species coupled to insights into their biological activities. Furthermore, we present an example of the annotation of key genes involved in polyphenolic biosynthesis in peanut using comparative genomics as a case study outlining how we are approaching omics-based approaches of the nut plant species.